2010
DOI: 10.1007/s00425-010-1294-7
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of Arabidopsis plants in response to allelochemical l-DOPA

Abstract: Velvetbean (Mucuna pruriens) plants impede the growth of neighboring plants. One compound, 3-(3',4'-dihydroxyphenyl)-L-alanine (L-DOPA), is responsible for the allelopathic capacity of velvetbean. This compound is an active allelochemical that decreases root growth of several plant species. In mammals, L-DOPA is a well-known therapeutic agent for the symptomatic relief of Parkinson's disease. However, its mode of action in plants is still not well understood. To address such issues, gene expression in Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…The authors suggested that the mode of action of L-DOPA may be related to changes in amino acid metabolism and iron homeostasis, important for many fundamental biological processes such as photosynthesis. 40 Additionally, L-DOPA also seems to mimic amino acid analogs, with subsequent incorporation into proteins. 26 In fact, the binding of L-DOPA to tyrosyl and phenylalanyltRNA synthetases has been observed in bacterial and prokaryotic-eukaryotic cells, respectively, 41 including mammalian cells in vitro.…”
Section: Effects Of L-dopa In Plantsmentioning
confidence: 99%
“…The authors suggested that the mode of action of L-DOPA may be related to changes in amino acid metabolism and iron homeostasis, important for many fundamental biological processes such as photosynthesis. 40 Additionally, L-DOPA also seems to mimic amino acid analogs, with subsequent incorporation into proteins. 26 In fact, the binding of L-DOPA to tyrosyl and phenylalanyltRNA synthetases has been observed in bacterial and prokaryotic-eukaryotic cells, respectively, 41 including mammalian cells in vitro.…”
Section: Effects Of L-dopa In Plantsmentioning
confidence: 99%
“…13,14) It has been used to monitor changes in transcript levels in response to various allelochemical stresses on a whole-genome scale. 9,15,16) Presently, new agrochemicals are required to control weed strains that are resistant to commercial herbicides, but evaluating promising chemical derivatives is labor intensive and time consuming. DNA microarray analysis is potentially an efficient and rapid tool for evaluating the bioactivities of chemical derivatives.…”
Section: )mentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) analysis was performed as described (Golisz et al 2011) to investigate the expression of particular genes in shoots and roots over time, and to validate our microarray data sets. Plants were treated with 20 µM cis-CA, 20 µM IAA, or nothing (control).…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…Guo et al (2011) identified two cis-CA-upregulated Arabidopsis genes, MLPL1 (AT2G01520) and MLPL2 (AT2G01530). DNA microarray analysis could serve as an effective tool to investigate the mode of action of cis-CA, considering that it has been used to monitor changes in response to other allelochemical stresses in the transcription state of individual Arabidopsis genes on a whole-genome scale (Baerson et al 2005;Golisz et al 2011). In the present study, we reveal for the first time the Arabidopsis genes upregulated by exogenous cis-CA, using a DNA microarray and Gene Ontology enrichment analysis.…”
mentioning
confidence: 93%